Investigation of the frequency of hyperuricemia and associated risk factors in patients with psoriatic arthritis - Yilmaz, Ebru; Pasin, Özge; Pasin, Tugçe (International Journal of Research in Medical Sciences, 2025)
Background: This study aimed to determine the frequency of and clinical significance of hyperuricemia in psoriatic arthritis (PsA) patients. Methods: The study included 63 PsA patients. Characteristics of the patients, psoriasis (Pso) and PsA duration, and co-morbidities such as hypertension, diabetes mellitus, dyslipidemia, hypothyroidism and coronary artery disease were collected. Moreover, serum uric acid (SUA) and C-reactive protein (CRP) levels at the time of diagnosis, psoriasis area and severity index (PASI) score, body surface area (BSA), Disease Activity index for Psoriatic Arthritis (DAPSA), and Bath Ankylosing Spondylitis Radiological Index (BASRI-total) score were also recorded. Results: The mean age of the patients was 46.2±10.6 years. 28 (44.4%) had hyperuricemia, of which 23 (36.5%) were female and 5 (7.9%) were male. The mean SUA level was significantly higher in male patients (p=0.002), whereas hypertension was more prominent in female patients (p=0.010). There was no significant relationship between hyperuricemia and BSA, PASI and DAPSA score. PsA patients with hyperuricemia had a high significant difference in BMI (p=0.045) and hypertension (p=0.044). BASRI score was significantly related to age, body mass index, DAPSA score, plantar fascia, greater trochanter, and the Achilles enthesitis (p<0.001, p=0.005, p=0.001, p=0.015, p=0.016 and p=0.031, respectively). On regression analysis, only BMI was associated with SUA level (p=0.043). Conclusions: The majority of PsA patients had asymptomatic hyperuricemia. Moreover, hyperuricemia was associated with BMI and hypertension. The higher rate of hyperuricemia in women than men seems to be due to their higher BMI values.